Alternariol as virulence and colonization factor of Alternaria alternata during plant infection. Issue 1 (23rd April 2019) - Wenderoth, Maximilian; Garganese, Francesca; Schmidt‐Heydt, Markus; Soukup, Sebastian Tobias; Ippolito, Antonio; Sanzani, Simona Marianna; Fischer, Reinhard
Summary: The filamentous fungus Alternaria alternata is a potent producer of many toxic secondary metabolites, which contaminate food and feed. The most prominent one is the polyketide‐derived alternariol (AOH) and its derivative alternariol monomethyl ether (AME). Here, we identified the gene cluster for the biosynthesis of AOH and AME by CRISPR/Cas9‐mediated gene inactivation of several biosynthesis genes in A. alternata and heterologous expression of the gene cluster in Aspergillus oryzae . The 15 kb‐spanning gene cluster consists of a polyketide synthase gene, pksI, an O‐methyltransferase, omtI, a FAD‐dependent monooxygenase, moxI, a short chain dehydrogenase, sdrI, a putative extradiol dioxygenase, doxI and a transcription factor gene, aohR . Heterologous expression of PksI in A. oryzae was sufficient for AOH biosynthesis. Co‐expression of PksI with different tailoring enzymes resulted in AME, 4‐hydroxy‐alternariol monomethyl ether (4‐OH‐AME), altenusin (ALN) and altenuene (ALT). Hence, the AOH cluster is responsible for the production of at least five different compounds. Deletion of the transcription factor gene aohR led to reduced expression of pksI and delayed AOH production, while overexpression led to increased expression of pksI and production of AOH. The pksI ‐deletion strain displayed reduced virulence on tomato, citrus and apple suggesting AOH and the derivatives as virulence and colonization factors. Abstract : Alternaria alternata contaminates many crops and fruits. The mold produces a large variety of different mycotoxins, one of which is alternariol and its derivatives. We identified the gene cluster responsible for their biosynthesis and show that alternariol is a colonization and virulence factor on tomato, apple and citrus.